The effect of Instagram on eating behaviour - Zhao, Cecilia Lingxin (2018)
Social media usage has been found to be associated with greater body dissatisfaction and disordered eating, with majority of research focusing on Facebook use. The aim of this study was thus to examine the relationship between Instagram use, body dissatisfaction, and eating behaviours. The sample consisted of 56 university students. The Instagram group browsed their own Instagram home feed while the control group viewed standardised images of science and education. All participants then reported their body dissatisfaction level, and were subsequently served potato chips to consume while watching a short documentary. We found that Instagram use in a naturalistic manner (browsing one’s own home feed) does not result in significantly greater body dissatisfaction among men and women. Female participants had significantly greater body dissatisfaction than male participants. Instagram use resulted in significantly greater consumption of snacks than exposure to standardised science and education images. Moreover, following exposure to Instagram use, participants who had higher body dissatisfaction consumed significantly less chips than those with lower body dissatisfaction. These results were most prominent among women who perceived their current body to be larger than ideal (wanting to be slimmer). Consequently, this study demonstrates that Instagram use influences eating behaviour, and that this relationship is moderated by an individual’s level of body dissatisfaction.